Strategi Dinas Sosial Kota Makassar Dalam Upaya Penanganan Anak Jalanan - Sakir, Ahmad Rosandi; Amaliah, Yusriah; Lukman, Juwita Pratiwi; Rajab, Marlina (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
The aim of this research is to gain an understanding of the strategies employed by the Department of Social Affairs in addressing street children in the city of Makassar, including the supporting and inhibiting factors influencing the implementation of these strategies. The research conducted is qualitative and descriptive in nature, utilizing sociological and communication approaches, with observation and interview techniques. Primary data sources include information obtained through direct observation at the research location and interviews, while secondary data is derived from documentation, mass media, and journals.The research findings indicate that the strategies of the Makassar City Social Affairs Department align with Regional Regulation No. 2 of 2008 related to the guidance of street children, homeless individuals, street musicians, and beggars. The department addresses these social issues through data collection activities and providing guidance. However, there are several obstacles in dealing with street children, such as the absence of facilities or rehabilitation centers in Makassar that can accommodate street children for personal development, aiming to reduce the number of street children in the area.